Subduction signature of the Vardar ophiolite of North Macedonia: new constraints from geochemical and stable isotope data - Brombin, Valentina; Barbero, Edoardo; Saccani, Emilio; Precisvalle, Nicola; Lepitkova, Sonja; Milevski, Ivica; Ristovski, Igor; Milcov, Igor; Dimov, Gorgi; Bianchini, Gianluca (Ofioliti, 2022)
Volatiles such as carbon (C) and sulphur (S) are commonly transferred into the mantle from subduction of oceanic lithosphere and overlying sediments. C and S isotopic signatures of magmatic rocks could be used as proxies of the slab components involved in the petrogenesis of subduction-related ophiolites. Therefore, in this work we investigated the major and trace element composition, as well as the C and S elemental contents and isotopic ratios (13C/12C and 34S/32S) of subvolcanic and volcanic rocks of the Vardar ophiolites of North Macedonia, which represent the remnants of the Mesozoic Tethyan oceanic lithosphere formed in supra-subduction zone tectonic settings. The ophiolites were sampled at Lipkovo and Demir Kapija localities, in the northern and southern part of North Macedonia, respectively. Based on whole-rock major and trace element composition, three groups of rocks can be distinguished: i) Group 1 rocks, which are subalkaline basalts having backarc affinity, ii) Group 2a and iii) Group 2b rocks, which are calc-alkaline basalts having arc affinity, with and without adakitic signatures, respectively. The qualitative petrogenetic models indicate that studied rocks formed by partial melting of mantle sources variably metasomatized by subduction-related components, such as aqueous fluids, sediment melts, and adakitic melts. Accordingly, all the North Macedonia ophiolites are characterized by C and S signatures which deviate from those typical for mantle and Mid Ocean Ridge melts. The variably low δ13C values recorded by Group 1 and 2 rocks could be related to the different contributions of melts released by subducting sediments rich in organic matter. However, we cannot exclude that such C-enriched signature is the result of isotopic fractionation during degassing process. In contrast, the enriched S isotopic signatures of the North Macedonia ophiolites suggest a major involvement of melts derived from the subducting sediments rich in sulphate phases. In particular, the calc-alkaline basalts of Group 2 rocks record more positive δ34S values than the subalkaline basalts of Group 1 formed in backarc basin suggesting that the subarc mantle sources were more affected by slab-released fluids than those of the backarc basin, which were more distal from the trench.